The Impact of Punishment and Rehabilitation Views on Organizational Commitment Among Correctional Staff: A Preliminary Study - Lambert, Eric (American journal of criminal justice, 2008)
It has been long recognized that organizational commitment is an important component of effective organizations. It has, however, received relatively little attention in the correctional literature. Furthermore, much of the research to date on correctional orientation has focused on examining how various forces affect the punishment and rehabilitation views of correctional employees, but ignored how these views affect employees’ organizational commitment. Using a data set collected from 272 staff members at a Midwestern, high security state prison, this study examined the impact of punishment and rehabilitation views on organizational commitment. It was found that support for rehabilitation was associated with higher levels of organizational commitment while support for punishment was related with lower levels of organizational commitment.